An end is in sight: a perspective on PCR as an endpoint for Chagas disease treatment trials - Hochberg, Natasha S.; Rao, Srinivasa P. S.; Angyalosi, Gerhild; Zhao, Xiaojun; Carballo, Leticia; Demacq, Caroline; Braud-Perez, Sofia; Wieser, Daniela; Casas, JP; Millholland, John; Ngo, Debby (Frontiers in Parasitology, 2023)
Novel therapies for chronic indeterminate Chagas disease (CICD) are needed, but trials are limited by the absence of tests to detect infection and early treatment efficacy. This perspective highlights the shortfalls and strengths of polymerase chain reaction (PCR) as a study endpoint for anti-parasitic drug development. Serologic reversion, the gold standard test of cure, may take decades to occur in adults and therefore is challenging as an endpoint for drug development. Use of PCR as a marker of infection and treatment response has notable limitations due to low parasitemia in CICD, fluctuations in circulating (versus tissue) parasite burden, strain differences, and assay performance. It is, however, rapidly responsive to therapy, and technological advances have improved detection of different strains and may allow for parasite quantification. Until we have more sensitive tests for parasitological clearance, PCR as a measure of treatment failure may be the best available efficacy endpoint to accelerate early development of much-needed novel therapies. Adequately designed clinical studies are needed to correlate PCR clearance with clinical outcomes and to identify novel biomarkers predictive of clinical outcomes in patients with CICD. Public-private partnerships and health authority engagement are paramount to identify feasible trial endpoints and deliver promising new drug candidates for Chagas disease.